Identification of Majapahit Leaf Infusion Compounds (Crescentia Cujete L.) with LC-MS and Toxicity Analysis of Artemia Salina Leach - Martha, Rahma Diyan; Tilarso, Dara Pranidya; Adisyaningrum, Ega Nurgia (Fakultas Teknik Universitas Wahid Hasyim, 2024)
Cancer is a disease causes by the growth of cells that are not benign and have the ability to invade and metastasize. One of the plants that has potential as herbal medicine is the Majapahit plant (Crescentia Cujete L.). This research is useful for knowing the content of compound metabolites that have anticancer activities in majapahit leaf infusion used LC-MS, and to knowing the level of acute toxicity (LC50) on majapahit leaf infusion to Artemia Salina Leach with BSLT method. The majapahit leaf extract was obtained using the infusion method by dissolving in distilled water at 90oC for 15 minutes. Toxicity test was carried out onÂ concentration range of 100, 200, 300, 400, 500, 600, 700, 800, 900, and 1000 ppm which were tested on Artemia Salina Leach during 24 hours. The results of testing the majapahit leaf infusion extract using LC-MS found 3 compounds having the highest concentrations is, Narirutin 4'-glycoside, Kaempferol 3-[6â€-(3-hydroxy-3-methylglutaryl)glucoside] and, acacetin 7-rutinoside. The toxicity test of the acute extract of majapahit (Crescentia Cujete L.) leaf infusion using the BSLT method yielded an LC50 value of 792.8664 ppm. From the LC50 value obtained, it can be significant that the extract of majapahit leaf infusion has the potential as an anticancer by being labeled with an acquisition value of LC50 <1000 ppm.Â